The Criminal Law Enforcement Against Perpetrators of Motor Vehicle Theft with Violence in the Perspective of Certainty and Justice (A Study of Decision Number 651/Pid.B/2025/PN Tjk) - Hartono, Bambang; Seftiniara, Intan Nurina; Febriansyah, M. Abi (The Future of Education Journal, 2026)
The crime of motor vehicle theft with violence is a criminal phenomenon that is very disturbing to the community because it not only threatens property, but also the safety of life. This study aims to analyze the factors causing the crime of motor vehicle theft with violence, and law enforcement efforts based on (Study of Decision Number 651 / Pid.B / 2025 / PN Tjk) the mechanism of criminal law enforcement against perpetrators of theft with violence and evaluate the implementation of law enforcement in achieving the value of legal certainty and justice. The problems in this study are: the factors causing the crime of motor vehicle theft with violence based on decision number 651 / Pid.B / 2025 / PN Tjk. and criminal law enforcement against perpetrators of motor vehicle theft with violence based on decision number 651 / Pid.B / 2025 / PN Tjk. The research method uses a normative juridical and empirical juridical approach. The normative juridical approach is taken through a literature study by examining relevant laws and regulations, doctrines, and legal literature. Meanwhile, an empirical approach is carried out by interviewing parties involved or directly understanding the case in order to obtain a factual picture regarding the application of the law in the field. The results of the study indicate that the factors causing this crime come from internal aspects in the form of economic factors, education, religion, personality as well as external aspects which include the influence of family, environment, culture or habits. Regarding law enforcement, it has been carried out appropriately, and in accordance with the mechanisms of criminal procedure law. This can be seen from several aspects: the fulfillment of all elements of Article 363 paragraph (1) 4.5 of the Criminal Code, the Public Prosecutor assesses that the elements of the crime have been completely proven, and states that the perpetrator consciously committed his actions as a perpetrator of motor vehicle theft, the Panel of Judges issued a verdict based on the belief obtained from evidence, evidence and statements from witnesses and the perpetrator. The suggestion from this study is that law enforcement officers increase their accuracy in conducting examinations and eradicating criminal acts such as theft.